Place matters: return intentions among forcibly displaced young Georgians from Abkhazia living in Tbilisi and Zugdidi. Issue 2 (3rd May 2016) - Lundgren, Minna
ABSTRACT: Around 250, 000 people are internally displaced within Georgia today as a consequence of violent conflicts in Abkhazia and South Ossetia in the early 1990s and the Georgian-Russian war in 2008. The majority of the internally displaced persons originate from Abkhazia, which declared independence in 1999. While the conflict is still unresolved, the majority of those who fled remain displaced, most of them living in the vicinity of the capital Tbilisi, or in Zugdidi and the Samegrelo region bordering Abkhazia. The aim of this article is to study factors that impact on young people's intentions to return to Abkhazia, with a focus on youth presently living in the Tbilisi and Zugdidi areas. The study is based on a quantitative survey ( n  = 131) with youth aged 18–25 years, who were displaced when very young, or who were born in displacement, have few or no memories of prior residences, and may have different opinions on returning from their parents. A chi-square analysis was used to measure differences among the respondents' intentions to return permanently to Abkhazia withinx five years, in relation to their reasons for returning and factors in the past and the present. There was a significant association between return intentions and the current place of residence (Tbilisi or Zugdidi), with Tbilisi respondents more inclined towards return. Separate chi-square analyses for the two cities showed that different factors (birthplace, property in Abkhazia, socio-economic conditions, reasons for return and so on) have different impact on the return intentions of the respondents from the two cities, which allows us to conclude that place matters in thinking about post-conflict return trajectories.